Public policies and strategies of a complex system: the change in the urban mobility system of Bogotá - Meyer, Bernardo; Meyer Jr., Victor (Revista de Administração da UFSM, 2021)
Purpose – Urban mobility is one of the most relevant themes in discussions regarding quality of life in large urban centers worldwide. It is a challenge that local governments have been facing due to a significant growth in the urban population. The purpose of this study is to analyze the changes in public transport made by the local government in the city of Bogotá, Colombia Design/methodology/approach – It is an in-depth case study of a qualitative nature, based upon primary (interviews and observation) and secondary data. Data was collected in Brazil and Colômbia. Findings – The case signaled a significant change process by improving urban mobility through the implementation of successful public policies and strategies. The findings indicated that transforming a chaotic public transport system into a point of reference in this field is a notable effort. Practical implications – This study provides insights to public administrators that manage organizations that operate complex systems and pluralistic contexts Originality/value – This paper contributes to the field by discussing a unique case study in which the administration of a large capital of a South American country promoted a substantial change in the urban mobility system, tackling obstacles and developing an efficient approach.